Peran serta masyarakat desa dalam pembangunan - Ismani H. P. (Universitas Brawijaya, Fakultas Ilmu Administrasi, 1992)
Role of rural communities in village development; case study in Kedungrejo Village, Kecamatan Pakis, Kabupaten Malang, Jawa Timur Province.